2017
DOI: 10.3892/ol.2017.5690
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30e-3p inhibits cell invasion and migration in clear cell renal cell carcinoma by targeting Snail1

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common type of neoplasm affecting the adult kidney. Previous studies on ccRCC have focused on microRNAs, a class of small non-coding RNAs that are important in cancer development and progression. The present study aimed to investigate the potential role of microRNA (miR)-30e-3p in ccRCC. The results revealed that overexpression of miR-30e-3p in the A498 and 786O ccRCC cell lines was able to inhibit cell invasion and migration. The expression level of Snail1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“… 43 In addition, a recent study suggested that Snai1 was a direct target of miR-30e-3p in clear cell renal cell carcinoma. 44 Taken together, these findings support the notion that miR-30e may be involved in a number of pathological processes and human diseases through mediating the expression of Snai1.…”
Section: Discussionsupporting
confidence: 73%
“… 43 In addition, a recent study suggested that Snai1 was a direct target of miR-30e-3p in clear cell renal cell carcinoma. 44 Taken together, these findings support the notion that miR-30e may be involved in a number of pathological processes and human diseases through mediating the expression of Snai1.…”
Section: Discussionsupporting
confidence: 73%
“…no. ab52894; 1:50; Abcam) monoclonal antibodies, as previously described (20). The expression level was analyzed from images obtained using a light microscope (magnification, x200) from five random fields of view.…”
Section: Protein-protein Interaction (Ppi) Network Construction and Amentioning
confidence: 99%
“…The expression level was analyzed from images obtained using a light microscope (magnification, x200) from five random fields of view. Immunoblot assays were performed as previously described (20). Primary antibodies included those targeted against phosphorylated (p)-EGFR (cat.…”
Section: Protein-protein Interaction (Ppi) Network Construction and Amentioning
confidence: 99%
“…27), the most prevalent histological subtype, accounting for 70% to 80% of all RCC cases (28). For example, miRNAs have been implicated in different cellular processes in ccRCC, including proliferation, migration, invasion, and apoptosis (29,30). Recently, Yoshino and colleagues (31) targeted the two versions of miR-210, miR-210-3p and miR210-5p, employing the CRISPR/Cas9 system in three renal cell carcinoma (RCC) cell lines (786-o, A498 and Caki2).…”
Section: Renal Cell Carcinomamentioning
confidence: 99%